Production and Quality Evaluation of MASA Made From Maize, Rice and Millet Fortified With Soybean and Tigernut - I. G, Lawrence (International Journal of Scientific Research and Management (IJSRM), 2022)
This work was aimed to evaluate the quality of masa produced from rice, maize, millet fortified with soybean and tigernut. The proximate and sensory evaluation analyses were carried out on the masa samples for the whole grains and as well as the enriched masa samples. While functional properties were carried out on the flour produced. The result of the proximate composition showed that lowest moisture value (14.00%) was recorded for sample A among the enriched ‘masa’ samples while 12.75% was recorded for sample E among the whole samples which is good for shelf life stability. Sample C had the highest crude protein (7.87%), sample B had the highest fat content (32.03%), and sample A had the highest fibre (0.16%) and carbohydrate (57.56%). The bulk density, water absorption capacity, oil absorption capacity, swelling capacity and gelation concentration were within the range; 0.64-0.81g/ml, 123.33-180.57%, 93.57-142.21%, 47.67-125.33%, 0.20-0.60g respectively. The sensory evaluation showed that with regards to taste, texture, colour, appearance, aroma and overall acceptability sample B was more preferred among the enriched ‘masa’ samples and sample E was more preferred among the whole samples. Enrichment of ‘masa’ could contribute to improvement of nutritional status if promoted as a nutritious, health indigenous snack not only where ‘masa’ is already widely consumed, but also in other parts of Nigeria where it has not found wide acceptance.